Synchronization control scheme for gait training robot and treadmill - Tarapong Karnjanaparichat (2018)
© 2014 IEEE. Presently, gait training robots with treadmills have been widely used. If the robot and the treadmill lack of an appropriate synchronization, it may affected the performance of the whole system and foot slips on a moving treadmill may cause injuries to patients. Treadmill speed cannot be simply set as constant because foot speed is not constant throughout a gait cycle and the treadmill speed must only be the same as the touching foot in stance phase and the foot speed in swing phase must be ignored. This paper proposes a synchronization control scheme for a two-legged gait training robot and a treadmill. The treadmill speed is calculated based on the horizontal velocities of the left and right feet during the stance phase in order to adjust the treadmill speed. The effectiveness of the proposed synchronization method is confirmed by sixteen experimental tests with five healthy and three patient subjects.